Business cases for energy storage with multiple service provision - Teng,F; Strbac,G (Journal of Modern Power Systems and Clean Energy, 2016)
Energy storage (ES) has been considered as the key source of flexibility to support the integration of renewable energy. Previous studies have demonstrated the substantial system cost savings by the deployment of ES, including both investment and operation of generation, transmission and distribution infrastructure. However, this societal benefit may not be realized if industry actors do not have a viable business case to appropriately capture these multiple value streams. In this context, this paper investigates the value that ES may deliver to its owner over two specific business cases in a 2030 UK system. Firstly, the application of large-scale ES in the wholesale market is analysed. It is demonstrated that the optimal allocation of ES to provide multiple services is the key element for ES to become competitive in the electricity market. In the second business case, this paper analyses the value of kilowatt-scale ES combined with roof photovoltaic (PV) system in the household and community level. The study shows that multiple service provision of ES through advanced pricing schemes, for example time-of-use (ToU) tariff and dynamic distribution use of system (DUoS), lead to higher value and the coordination in the community level could further justify the application of domestic ES.